PENGENALAN LITERASI FINANSIAL MELALUI KEGIATAN MARKET DAY DI PAUD ISLAM DARUSSALAM PALANGKA RAYA - Melisa Melisa; Amelia Safitri; Kamelia Dewi; Deliana Nur Azizah; Aghnaita Aghnaita; Abdul Aziz (Kreasi: Jurnal Pengabdian Masyarakat, 2025)
Market day activities are a form of edupreneurial activity that can be carried out by early childhood. Through this activity, children are also introduced to edupreneurial values that can be implemented in everyday life. The purpose of this community service activity is to introduce financial literacy through market day activities at PAUD Islam Darussalam Palangka Raya. The method used is service learning with the subjects involved being students at PAUD Islam Darussalam Palangka Raya. The results of this community service activity are that children participate in market day with guidance from teachers. Some children act as sellers, and others play the role of buyers. The children are enthusiastic and motivated by the market day activities. This activity also fosters an entrepreneurial spirit, trains independence, self-confidence, and introduces children to the value of currency.